2012
DOI: 10.21273/hortsci.47.12.1821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cold Hardiness in Seven Iranian Commercial Pomegranate (Punica granatum L.) Cultivars

Abstract: Freezing injury is one of the most important limiting factors in commercial pomegranate production. The objectives of this study were to compare cold hardiness of seven Iranian pomegranate cultivars at three stages: November, January, and March, and to investigate the relationship between freezing tolerance and soluble carbohydrate and proline changes of shoots during acclimation and deacclimation. LT50 values, estimated by both electrolyte leakage measurement (EL LT50 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Means were compared using Duncan's multiple range test at the 5% level of significance (P ≤ 0.05). Correlation coefficients between soluble carbohydrate, proline, and protein concentrations and both EL-LT 50 and T-LT 50 values, estimated by electrolyte leakage and the tetrazolium stain test, were calculated using Pearson's correlation coefficient (Ghasemi Soloklui et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Means were compared using Duncan's multiple range test at the 5% level of significance (P ≤ 0.05). Correlation coefficients between soluble carbohydrate, proline, and protein concentrations and both EL-LT 50 and T-LT 50 values, estimated by electrolyte leakage and the tetrazolium stain test, were calculated using Pearson's correlation coefficient (Ghasemi Soloklui et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the activity of carbohydrate-metabolising enzymes, and the accumulation of carbohydrates, could be induced by K + ions. Yuanyuan et al (2009) andGhasemi Soloklui et al (2012) found a linear relationship between carbohydrate concentration and cold-hardiness, implying that the osmotic effect of carbohydrates probably prevented freezing injury in plants.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Despite numerous studies on cold stress responses in woody plants, there is little information on pomegranate responses to frost stress. Ghasemi Soloklui et al (2012) studied stem frost hardiness among seven 5-year-old pomegranate genotypes during one annual cycle and reported some of the tolerant and sensitive genotypes. They concluded that the content of soluble carbohydrates, especially from fall to mid-winter, is the best indicator of hardiness but, to date, the frost hardiness of mature pomegranate trees has not been reported.…”
Section: Introductionmentioning
confidence: 99%